PENGARUH TRANSPARANSI, GOOD SCHOOL GOVERNANCE, DAN PENGAWASAN TERHADAP EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (Studi Kasus SD Negeri Kabupaten Sukoharjo) - Chintya noer cahyani; Darmanto; Suprihati (Jurnal Akuntansi dan Pajak, 2027)
The purpose of this study was to determine the effect of transparency, good school governance, and supervision on the effectiveness of school operational fund management (BOS). The sampling method used in this study was random sampling with Slovin calculation. The sample size for this study was 80 respondents. The respondents were BOS treasurers of public elementary schools in Sukoharjo Regency. This research was quantitative, using primary data sources. Based on the results of primary data processing using multiple linear regression analysis, F-tests, and t-tests, it was found that transparency had a negative and significant effect on the effectiveness of school operational fund management, while good school governance and supervision had a positive and significant effect on the effectiveness of school operational fund management).